Long-term Metabolic Morbidity and Steatohepatosis Following Standard Pancreatic Resections and Parenchyma-sparing, Local Extirpations for Benign Tumor: A Systematic Review and Meta-analysis. Issue 1 (January 2022) - Beger, Hans G.; Mayer, Benjamin; Vasilescu, Catalin; Poch, Bertram
Abstract : Objective: To assess metabolic dysfunctions and steatohepatosis after standard and local pancreatic resections for benign and premalignant neoplasms. Summary of Background Data: Duodenopancreatectomy, hemipancreatectomy, and parenchyma-sparing, limited pancreatic resections are currently in use for nonmalignant tumors. Methods: Medline, Embase, and Cochrane libraries were searched for studies reporting measured data of metabolic functions following PD, pancreatic left resection (PLR), duodenum-sparing pancreatic head resection (DPPHR), pancreatic middle segment resection (PMSR), and tumor enucleation (TEN). Forty cohort studies comprising data of 2729 patients were eligible. Results: PD for benign tumor was associated in 46 of 327 patients (14.1%) with postoperative new onset of diabetes mellitus (pNODM) and in 109 of 243 patients (44.9%) with postoperative new onset of pancreatic exocrine insufficiency measured after a mean follow-up of 32 months. The meta-analysis displayed pNODM following PD in 32 of 204 patients (15.7%) and in 10 of 200 patients (5%) after DPPHR [ P < 0.01; OR: 0.33; (95%-CI: 0.15–0.22)]. PEI was found in 77 of 174 patients following PD (44.3%) and in 7 of 104 patients (6.7%) following DPPHR ( P < 0.01;OR: 0.15; 95%-CI: 0.07–0.32). pNODM following PLR was reported in 107 of 459 patients (23.3%) and following PMSR 23 of 412 patients (5.6%) ( P < 0.01; OR: 0.20; 95%-CI: 0.12–0.32). Postoperative new onset of pancreatic exocrine insufficiency was found in 17% following PLR and in 8% following PMSR ( P < 0.01). pNODM following PPPD and tumor enucleation was observed in 19.7% and 5.7% ( P < 0.03) of patients, respectively. Following PD/PPPD, 145 of 608 patients (23.8%) developed a nonalcoholic fatty liver disease after a mean follow-up of 30.4 months. Steatohepatosis following DPPHR developed in 2 of 66 (3%) significantly lower than following PPPD ( P < 0.01). Conclusion: Standard pancreatic resections for benign tumor carry a considerable high risk for a new onset of diabetes, pancreatic exocrine insufficiency and following PD for steatohepatosis. Parenchyma-sparing, local resections are associated with low grade metabolic dysfunctions. Abstract : Supplemental Digital Content is available in the text